Accelerated loss of trunk muscle density and size at L1 vertebral level in male patients with COPD - Wang, Ying; Li, Sidong; Zhang, Zhenyi; Sun, Shiqi; Feng, Juntao; Chen, Jinbiao; Pei, Yigang; Peng, Xianjing (Frontiers in Endocrinology, 2022)
Background and Purpose: Weight loss and muscle mass loss are common in patients with chronic obstructive pulmonary disease (COPD). Muscle density and fat infiltration based on CT images may be more sensitive than muscle mass by DXA in the assessment of sarcopenia for COPD patients. However, the age-related changes of cross-sectional trunk muscle compositions based on lung CT scans are still unknown. Thus. we aimed to investigate over time the change in muscle density, size, and fat deposition of L1-level trunk muscles in patients with COPD. Materials and Methods: 129 male COPD patients with a second chest CT scan (from 2013-2019 to 2014-2020) were enrolled. The CT images at first and second CT scans are analyzed by OsiriX software. Trunk muscles at the level of the 1st lumbar vertebrae were selected for analysis. Attenuation of lumbar vertebrae 1 was also measured from chest CT images. The pulmonary function values were calculated based on forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC). Results: The mean age of the 129 patients with COPD was 69.7 years. The durations of COPD of this cohort were from 8-17 years. The mean area and density of L1 trunk muscles were 85.5 cm2 and 36.4 HU. At baseline, muscle area and density and vertebral density were negatively associated with age (p＜0.0001), while the intermuscular fat area and the fat infiltration ratio were not significantly associated with age (p＞0.05). The per-year loss of trunk muscle area was 2.83 cm2 (p＜0.0001) which accounts for 3.3% decrease per year, and the per-year decrease of trunk muscle density was 2.41 HU (p＜0.0001) which accounts for 6.6% decrease per year. The per-year increase of intermuscular fat in trunk muscles was 0.57 cm2 (p=0.006) which accounts for 11.1% increase per year. The bone density loss was 5.63 HU/per year (p＜0.0001). Conclusion: Men with COPD had accelerated muscle loss as well as increased fat infiltration. Compared to muscle quantity loss, the decline in muscle quality is much larger, indicating the importance of relevant interventions focusing on improving muscle quality.